First Implantation of Silicon Nanopore Membrane Hemofilters. Issue 4 (July 2016) - Kensinger, Clark; Karp, Seth; Kant, Rishi; Chui, Benjamin W.; Goldman, Kenneth; Yeager, Torin; Gould, Edward R.; Buck, Amanda; Laneve, David C.; Groszek, Joseph J.; Roy, Shuvo; Fissell, William H.
Abstract : An implantable hemofilter for the treatment of kidney failure depends critically on the transport characteristics of the membrane and the biocompatibility of the membrane, cartridge, and blood conduits. A novel membrane with slit-shaped pores optimizes the trade-off between permeability and selectivity, enabling implanted therapy. Sustained (3–8) day function of an implanted parallel-plate hemofilter with minimal anticoagulation was achieved by considering biocompatibility at the subnanometer scale of chemical interactions and the millimeter scale of blood fluid dynamics. A total of 400 nm-thick polysilicon flat sheet membranes with 5–8 nm × 2 micron slit-shaped pores were surface-modified with polyethylene glycol. Hemofilter cartridge geometries were refined based on computational fluid dynamics models of blood flow. In an uncontrolled pilot study, silicon filters were implanted in six class A dogs. Cartridges were connected to the cardiovascular system by anastamoses to the aorta and inferior vena cava and filtrate was drained to collection pouches positioned in the peritoneum. Pain medicine and acetylsalicylic acid were administered twice daily until the hemofilters were harvested on postoperative days 3 (n = 2), 4 (n = 2), 5 (n = 1), and 8 (n = 1). No hemofilters were thrombosed. Animals treated for 5 and 8 days had microscopic fractures in the silicon nanopore membranes and 20–50 ml of transudative (albumin sieving coefficient θ alb 0.5 – 0.7) fluid in the collection pouches at the time of explant. Shorter experimental durations (3–4 days) resulted in filtration volumes similar to predictions based on mean arterial pressures and membrane hydraulic permeability and ( θ alb 0.2 – 0.3), similar to preimplantation measurements. In conclusion, a detailed mechanistic and materials science attention to blood–material interactions allows implanted hemofilters to resist thrombosis. Additional testing is needed to determine optimal membrane characteristics and identify limiting factors in long-term implantation.